Human Capital and Sustainable Development in a Religious Context - Kulzhanova, Gulbaram; Kulzhanova, Zhuldizay; Efimovа, Larisa (Journal of Ethnic and Cultural Studies, 2021)
The purpose of the study is to evaluate the impact of human capital (HC) on the sustainable development of a country or region through the prism of religious values. The following indicators were used for the analysis: Human Development Index, GDP per Capita, and Adult Mortality Rates in Orthodox Russia, Muslim, and Orthodox Kazakhstan, and developed countries dominated by Protestant religion, such as the United States, the United Kingdom, and Germany. The results show that differences in socio-economic growth between countries exist because the religions and cultures that influence those countries are different. Russia’s and Kazakhstan’s delay in capitalizing human capital may be provoked by the difference in the attitude these two countries have towards labor compared to other countries chosen for the study. The high quality of formal education in Russia and Kazakhstan is largely offset by a negative Orthodox and Muslim attitude to material achievements and financial prosperity. Orthodox representatives perceive individual wealth and career aspirations as sin and arrogance. The results of the study may be useful in teaching cultural disciplines.